High spin levels in 119Te - Papadopoulos, C. T.; et al., - (HNPS Advances in Nuclear Physics, 2020)
High spin levels in 119Te have been populated following the 96Zr(30Si,α3n)119Te reaction at a beam energy of 135 MeV. The subsequent deexcitation was studied using γ-ray spectroscopic methods. New levels and several spin and parity assignments up to Jπ=55/2- were established. The decay scheme is characterized by single particle excitations. For the 39/2- level the fully aligned v(h11/2)^3 π(g7/2)^2 configuration is proposed, while the 55/2- level could be associated with the π(d5/2)^2 ν(h11/2)^5(g7/2)^-2 configuration.